2009
DOI: 10.1097/bsd.0b013e3181884940
|View full text |Cite
|
Sign up to set email alerts
|

Coronal and Sagittal Plane Correction in Patients With Lenke 1 Adolescent Idiopathic Scoliosis

Abstract: Interval pedicle screw placement constructs seem to be equally effective as consecutive constructs for facilitating curve correction in patients with Lenke 1 AIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 24 publications
5
35
0
3
Order By: Relevance
“…This finding agrees well with previous clinical reports [9,12] suggesting that interval pedicle screw placement constructs seem to be equally effective as consecutive constructs for facilitating curve correction in patients with Lenke 1 AIS [12]; higher implant density did not improve curve correction for patients with AIS operated by a single surgeon using an identical surgical technique and type of instrumentation [9]. However, a significant correlation has been found between the number of implants and the curve correction using a multi-center database of AIS patients [11].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This finding agrees well with previous clinical reports [9,12] suggesting that interval pedicle screw placement constructs seem to be equally effective as consecutive constructs for facilitating curve correction in patients with Lenke 1 AIS [12]; higher implant density did not improve curve correction for patients with AIS operated by a single surgeon using an identical surgical technique and type of instrumentation [9]. However, a significant correlation has been found between the number of implants and the curve correction using a multi-center database of AIS patients [11].…”
Section: Discussionsupporting
confidence: 94%
“…In order to apply certain correction techniques and to have a better control on the deformed spine, there has been a noticeable trend among spine surgeons to use more and more pedicle screws [9][10][11]. Nowadays, pedicle screws are frequently placed bilaterally at each vertebra included in the fusion, but some surgeons recommend fewer screws [12]. In spite of the demonstrated benefits of pedicle screws, the associated complications, risks, and the hardware costs are not negligible [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…3, 10,16,38 Although most surgeons would agree that placing 2 pedicle screws at every level fused is usually unnecessary for coronal curve correction, 4,7,17,21,25 the optimal implant density remains unknown. Especially when the sagittal plane has to be taken into consideration, to the best of our knowledge, insufficient evidence of optimal implant density is available to help with decision making.…”
mentioning
confidence: 99%
“…In the literature, the lowest mean implant density reported to have successful results is 1.06 screws per level fused. 21,32,34,50 Thus, 1.06 screws per level fused was then defined as very low implant density. Multiple models were considered.…”
Section: Methodsmentioning
confidence: 99%
“…57 Other studies of predominantly screw constructs have not found a significant difference in curve correction or other parameters. 32,34,48,50 conclusions Should low and high screw-density patterns be determined to have similar clinical and radiographic results, as shown by this model, even a modest reduction in the number of screws may result in significant cost savings of 4% to 7% for the payer. In addition, fewer malpositioned screws and a decreased return to surgery for screw malposition may improve patient safety and the quality of surgical care.…”
Section: Additional Literature On the Cost Savings From Using Low Impmentioning
confidence: 99%